AL-FAIL DAN BEBERAPA PERMASALAHANNYA DALAM BAHASA ARAB - Kasmiati, Kasmiati (Hunafa: Jurnal Studia Islamika, 2007)
In Arabic, a faâil is an ism marfuâ that occurs before its fiâil. Some of faâils are zhahir and some are mudhmar. A faâil exists only whenever there is a fiâil. However, there is a fiâil that must be omitted from its faâil since there is a sign denotes it. A faâil has seven ahkam. This article discusses the seven ahkam al-faâil in Arabic.Â Kata Kunci:Â  Ahkam al-Fail, faâil zhahir, faâil mudhmar, ahkam, mudzakkar dan muannats